PENINGKATAN KINERJA INDUSTRI KECIL DAN MENENGAHDENGAN PENDEKATAN MODEL ERGONOMI POSTUR KERJA - Syaeful Arief (JUTI UNISI, 2019)
Human factors are very important factors in small and medium industries, in determining the productivity of a production system. However, work safety and comfort are often overlooked, as happened in two different companies, namely food companies and manufacturing companies. Both are influenced by the conditions of the company's work facilities that are less ergonomic, so that they can endanger the body of the worker. A similar thing also happened to Manufacturing companies. This study aims to analyze and make a proposal for a more ergonomic work facility design using the Ergonimi pastoral approach. From the results of the improvement it was found that the risk level of Cumulative Trauma Disorders (CTD) was reduced from high to low and from high to moderate. While productivity of work time increases by 10-20%.